Dilemmas of empowering families of children with autism spectrum disorders: a qualitative case study. Issue 2 (5th October 2020) - Khara, Rouhallah; Kalankesh, Leila R.; Shahrokhi, Hassan; Dastgiri, Saeed; Gholipour, Kamal; Feizi-Derakhshi, Mohammad-Reza
Abstract : Purpose: The purpose of this study was to identify the challenges and solutions in the empowerment of families of children with autism in Tabriz located in the North West of Iran. Design/methodology/approach: In this exploratory and qualitative study, which was conducted from January to March 2019, 14 in-depth face-to-face interviews and 1 focus group ( n = 5) were conducted with family empowerment experts. Data analysis was performed based on a content analysis approach via MAXQDA v 10. Findings: Results revealed that empowerment challenges can be classified into six main themes including shortage of facilities and specialists, family-related problems, administrative and organizational, cultural and societal, financial and other problems. The most important empowerment solutions were divided into three main themes including informing and training skills by holding empowerment programs, governmental and insurance companies support, and organizational and administrative solutions. Research limitations/implications: Limitation of this study is that families are not included; as families may also provide or challenge other solutions for empowerment based on their needs, ignoring their views may be losing part of vital information in this field. It is recommended that this research be conducted in the future from the perspective of families of people with autism and other stakeholders. Practical implications: Based on the results of this study, stakeholders in the field of autism and the family empowerment can address the identified challenges and utilize solutions to improve the process of family empowerment and make more effective decisions in this regard. Originality/value: Literature searches revealed a lack of any completed research in Iran specific to identifying empowerment challenges and related solutions. Efforts must be taken on root challenges which have been identified scientifically.